Depacked patients who underwent a shortened perihepatic packing for severe blunt liver trauma have a high survival rate: 20 years of experience in a level I trauma center. Issue 3 (June 2022) - Martellotto, Sophie; Melot, Charlotte; Raux, Mathieu; Chereau, Nathalie; Menegaux, Fabrice
Abstract: Introduction: Non-operative management is currently the preferred approach in blunt liver trauma, including high grade liver lesions. However, hemodynamic instability imposes the need for an emergency laparotomy, with a perihepatic packing (PHP) to control liver bleeding in most cases. Our retrospective study aimed to assess the outcomes of liver trauma patients who underwent a shortened PHP. Methods: All consecutive patients who underwent PHP for blunt liver trauma from 1998 to 2019 in our Level I trauma center were included in the study. Unstable patients with severe liver trauma were transferred to the operating room without any delay, and a collective decision was made to perform abbreviated laparotomy to pack the liver. Demographics, perioperative data, postoperative outcomes, and mortality were retrospectively collected, and survivors and deceased patients were compared with a paired t-test. Results: Fifty-nine patients of 206 patients admitted with severe liver injuries were treated with shortened PHP. Thirty-four (57.6%) patients died, including 26 (76.5%) within the first 24 h. Twelve (20.3%) patients had a selective hepatic embolization and eight (13.6%) had an extrahepatic embolization. Forty-eight patients had an extra abdominal associated injury. This was not a predictive factor of mortality. The removal of packing was performed in 24 patients within 72 h after laparotomy, with an 80% survival rate in these patients. Conclusion: Shortened PHP is an effective strategy for controlling liver bleeding in severe hepatic trauma. The mortality rate of these patients is high, but after the removal of packing, the survival is good. Graphical abstract: Image 1 Highlights: Non-operative management is currently the preferred approach in blunt liver trauma. In case of hemodynamic instability the emergency laparotomy has to be performed. We conducted a retrospective study to assess the outcomes for these patients. The mortality rate is high, but after the removal of packing, the survival is good.